Critical reflections on nuclear and renewable energy : environmental protection and safety in the wake of the Fukushima nuclear accident - Kuo, Way, 1951- (Hoboken, New Jersey : John Wiley & Sons, 2014)
"The book analyses the pros and cons of a spectrum of energies, ranging from petroleum, coal, gas to water, solar and wind energies as well as nuclear energy in the wake of the Fukushima nuclear incident in 2011. It maintains that we should look at nuclear energy from a rational point of view instead of being influenced by emotions or politicians' arguments"--
Natural Calamities are Less Destructive than Man-made Accidents11 When Will Environmental Pollution End?; The Misleading and Mislabeling Food Products; The Ubiquity of Biological and Chemical Sources of Pollution; Non-nuclear Pollution Permeates the World; Coal-fired Pollution Shocks and Global Warming; Coal Mining; The Melancholic Beauty of Idaho; Which Way Forward: "Nuclear" or "Non-nuclear"?; Passengers and Taxi Drivers; 12 Non-nuclear Calamities Are Also Horrible; Natural Calamities; Man-made Disasters; Horrible Consequences.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Nuclear engineering -- Safety measures; Nuclear engineering -- Political aspects; Nuclear power plants -- Risk assessment; Renewable energy sources; SCIENCE / Energy; Energy policy; Nuclear energy; Renewable energy sources; Renewable energy; Nuclear engineering -- Political aspects; Nuclear engineering -- Safety measures; Nuclear power plants -- Risk assessment; Renewable energy sources; Electronic books; Electronic books